Distribution characteristics and migration patterns of hazardous trace elements in coal combustion products of power plants. (15th December 2019) - Wang, Jinxi; Yang, Zhen; Qin, Shenjun; Panchal, Balaji; Sun, Yuzhuang; Niu, Hongya
Graphical abstract: Highlights: The concentration of residual state has increased in combustion products. According to the enrichment index REI, hazardous elements can be classified into three categories. The elements left in slag are Cr, Mn and Ni, the rest are semi-volatile. The elements mainly volatilized into the atmosphere are few in the process of burning coal, only Sb. Abstract: Trace elements in coal produce migration and enrichment after combustion, the enrichment and release of hazardous trace elements will cause effective harmful to human health and the environment. In this paper, the distribution characteristics and occurrence state of hazardous trace elements in coal combustion products were studied by measuring the concentration of harmful trace elements in coal, slag, coarse ash, fine and fly ash. The experimental study of step-by-step chemical extraction was carried out, the migration and transformation model of trace elements in coal combustion process was investigated. The results show that the trace elements are easily enriched in fine particles of coal ash. The occurrence state of elements in combustion products has changed obviously, and the concentration of residual state has increased for example aluminosilicates. According to the enrichment index REI (Relative Enrichment Index), hazardous elements can be classified into three categories: (I) The elements left in both solid waste slag and fly ash are Cr, Mn and Ni (REI > 0.85); (II) The elements left in solid waste are Be, Co, Cu, Zn, Cd, Ba, Pb and U (0.1 < REI < 0.85); (III) The elements mainly volatilized into the atmosphere are few, only Sb (REI < 0.1).